Composite positive electrode material, preparation method thereof, positive electrode sheet, secondary battery, and battery module, battery pack and device containing the secondary battery

By using lithium-rich metal oxide as the core and positive electrode active material as the cladding layer in the positive electrode material of the secondary battery, the problem of irreversible capacity loss during the first charging and discharging process is solved, and a higher energy density and longer cycle life is achieved.

CN116114082BActive Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080102742.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-25
Publication Date
2025-03-07
Estimated Expiration
2040-11-25

AI Technical Summary

Technical Problem

During the first charging and discharging process, the secondary battery will lose irreversible capacity due to the formation of the SEI film, which will affect the increase of energy density.

Method used

A composite positive electrode material is used, wherein the core includes lithium-rich metal oxides, and the cladding layer includes a positive electrode active material. By surface-covering the positive electrode lithium supplement material, it isolates the external environment, and improves material stability and lithium supplement efficiency.

Benefits of technology

Effectively make up for the active lithium lost during the first charge and discharge of the battery, improve the first charge and discharge capacity and energy density of the battery, and significantly extend the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116114082B_ABST
    Figure CN116114082B_ABST
Patent Text Reader

Abstract

The present application provides a composite positive electrode material, a preparation method thereof, a positive electrode plate, a secondary battery, and a battery module, a battery pack, and a device comprising the secondary battery. The composite positive electrode material comprises a core and a coating layer covering at least a portion of the surface of the core, the core comprising a positive electrode lithium supplement material, the positive electrode lithium supplement material comprising a lithium-rich metal oxide, and the coating layer comprising a positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of energy storage devices, and specifically relates to a composite positive electrode material, a preparation method thereof, a positive electrode plate, a secondary battery, and a battery module, a battery pack and a device comprising the secondary battery. Background Art

[0002] In recent years, with the application and promotion of secondary batteries in various electronic products and new energy vehicles, their energy density has received more and more attention. However, during the first charge and discharge process of secondary batteries, the negative electrode inevitably forms a SEI (solid electrolyte interface) film, which causes active ion consumption. The irreversible capacity loss caused by this is difficult to eliminate, which brings challenges to the improvement of the energy density of secondary batteries. Summary of the invention

[0003] In a first aspect, the present application provides a composite positive electrode material, which includes a core and a coating layer covering at least a portion of the surface of the core, wherein the core includes a positive electrode lithium replenishing material, the positive electrode lithium replenishing material includes a lithium-rich metal oxide; and the coating layer includes a positive electrode active material.

[0004] This application, by coating the surface of the positive electrode lithium replenishing material with a positive electrode active material, can isolate the external environment, improve the stability of the material, ensure the purity of the material and the performance of lithium replenishment, and at the same time, the coating layer of the positive electrode active material is a good lithium ion conductor, thereby greatly improving the efficiency of lithium replenishment. Therefore, the use of the composite positive electrode material of this application can effectively make up for the active lithium lost during the first charge and discharge process of the battery, and can improve the first charge and discharge capacity of the battery, thereby improving the energy density. Furthermore, the form of coating the positive electrode lithium replenishing material with a positive electrode active material can avoid the introduction of additional inactive substances, which is conducive to making the battery obtain a higher energy density. Furthermore, the use of the composite positive electrode material of this application also significantly extends the cycle life of the battery.

[0005] In any embodiment of the present application, in the composite positive electrode material, the positive electrode active material is distributed on the surface of the core in the form of independent particles. The composite positive electrode material meets the above conditions, and the battery using it can obtain higher energy density and cycle performance.

[0006] In any embodiment of the present application, in the composite positive electrode material, the mass ratio of the positive electrode lithium supplement material to the positive electrode active material is 1:2 to 1:35, optionally 1:5 to 1:30, and further optionally 1:10 to 1:20. The mass ratio of the positive electrode lithium supplement material to the positive electrode active material within the above range can enable the battery to obtain higher energy density and cycle performance.

[0007] In any embodiment of the present application, the median particle size D of the positive electrode lithium supplement material isv 50 is 2 μm to 35 μm, optionally 5 μm to 30 μm, and further optionally 15 μm to 25 μm. D of positive electrode lithium supplement material v 50 Within an appropriate range, the capacity utilization rate of the positive electrode lithium supplement material can be improved, and the energy density and cycle performance of the battery can be further improved.

[0008] In any embodiment of the present application, the median particle size D of the positive electrode active material is v 50 is 0.1 μm to 15 μm, optionally 0.2 μm to 10 μm, further optionally 0.5 μm to 6 μm. D of the positive electrode active material v 50 Within an appropriate range, the energy density and cycle performance of the battery can be further improved.

[0009] In any embodiment of the present application, the lithium-rich metal oxide may be selected from Li 2 M 1 O 2 , Li 2 M 2 O 3 , Li 3 M 3 O 4 , Li 5 M 4 O 4 , Li 6 M 5 O 4 One or more of the following, where M 1 Including one or more of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, M 2 Including one or more of Mn, Sn, Mo, Ru, Ir, M 3 Including one or more of V, Nb, Cr, Mo, M 4 Including one or more of Fe, Cr, V, Mo, M 5 It includes one or more of Co, V, Cr, and Mo, and the average valence state of each metal element except Li in the lithium-rich metal oxide is lower than its own highest oxidation valence state.

[0010] In any embodiment of the present application, the lithium-rich metal oxide may be selected from Li 3 VO 4 , Li 2 MnO 2 , Li 3 NbO 4 , Li 5 FeO 4 , Li 6 CoO 4 , Li2 NiO 2 , Li 2 CuO 2 and Li 2 Cu x1 Ni 1-x1 M v1 O 2 One or more of, wherein 0<x1<1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.2≤x1≤0.8. Further optionally, 0.5≤x1≤0.7.

[0011] In any embodiment of the present application, the positive electrode active material can be selected from one or more of layered lithium transition metal oxides, spinel structured lithium metal oxides and polyanion type positive electrode materials. Optionally, the layered lithium transition metal oxide is selected from LiCoO 2 、LiNiO 2 、LiMnO 2 、LiNi a Co b Mn c O 2 、LiNi α Co β Al γ O 2 And one or more of their modified materials, wherein 0<a<1, 0<b<1, 0<c<1, a+b+c=1, 0<α<1, 0<β<1, 0<γ<1, α+β+γ=1. Optionally, the spinel structured lithium metal oxide is selected from LiMn 2 O 4 、LiNi 0.5 Mn 1.5 O 4 Optionally, the polyanion positive electrode material is selected from LiFePO 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 , Li 3 V 2 (PO 4 ) 3 、LiFe y Mn 1-y PO 4 And one or more of their modified materials, wherein 0<y<1, optionally 0.2≤y≤0.8.

[0012] In any embodiment of the present application, the positive electrode active material may be selected from LiFePO 4 、LiMnPO4 , Li 3 V 2 (PO 4 ) 3 And one or more of their modified materials.

[0013] In any embodiment of the present application, the charge cut-off voltage of the positive electrode active material is 4.2V to 5.2V (vs. Li / Li + ), the lithium-rich metal oxide may be selected from Li 6 CoO 4 , Li 5 FeO 4 , Li 2 NiO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 , Li 3 VO 4 , Li 3 NbO 4 One or more of, wherein 0<x1<1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.1≤x1≤0.9. Further optionally, 0.2≤x1≤0.8. Optionally, the positive electrode active material is selected from LiCoO 2 、LiNi a Co b Mn c O 2 、LiNi α Co β Al γ O 2 、LiMn 2 O 4 、LiNi 0.5 Mn 1.5 O 4 、LiCoPO 4 、LiNiPO 4 And one or more of their modified materials, wherein 0<a<1, 0<b<1, 0<c<1, a+b+c=1, 0<α<1, 0<β<1, 0<γ<1, α+β+γ=1.

[0014] Optionally, the median particle size D of the positive electrode active material v 50 is 1 μm to 15 μm, optionally 2 μm to 10 μm, and further optionally 4 μm to 6 μm. D of the positive electrode active material v 50 Within the above range, the energy density and cycle performance of the battery can be further improved.

[0015] In any embodiment of the present application, the charge cut-off voltage of the positive electrode active material is 3.5V to 4.2V (vs. Li / Li + ), the lithium-rich metal oxide may be selected from Li 5 FeO 4 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 , Li 2 MnO 2 One or more of, wherein 0<x1<1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.1≤x1≤0.9. Further optionally, 0.2≤x1≤0.8. Optionally, the positive electrode active material is selected from LiFePO 4 , Li 3 V 2 (PO 4 ) 3 and LiFe y Mn 1-y PO 4 One or more of, wherein 0<y<1. Optionally, 0.2≤y≤0.8.

[0016] Optionally, the median particle size D of the positive electrode active material v 50 is 0.1 μm to 3.5 μm, optionally 0.2 μm to 2 μm, and further optionally 0.5 μm to 1.5 μm. D of the positive electrode active material v 50 Within the above range, the energy density and cycle performance of the battery can be further improved.

[0017] The second aspect of the present application provides a method for preparing a composite positive electrode material, which comprises the following steps:

[0018] Providing a core, the core comprising a positive electrode lithium supplement material, the positive electrode lithium supplement material comprising a lithium-rich metal oxide;

[0019] Providing a coating material, wherein the coating material includes a positive electrode active material;

[0020] The coating material is coated on at least a portion of the surface of the core to obtain a composite positive electrode material.

[0021] In the preparation method provided by the present application, the positive electrode active material is coated on the surface of the positive electrode lithium replenishment material, which can isolate the external environment, improve the stability of the material, ensure the purity of the material and the performance of lithium replenishment, and at the same time, the positive electrode active material coating layer is a good lithium ion conductor, thereby greatly improving the efficiency of lithium replenishment. Therefore, the composite positive electrode material obtained by the preparation method of the present application can effectively make up for the active lithium lost during the first charge and discharge of the battery, improve the first charge and discharge capacity of the battery, and thus improve the energy density. Furthermore, the form of coating the positive electrode lithium replenishment material with a positive electrode active material can avoid the introduction of additional inactive substances, thereby enabling the battery to obtain a higher energy density. Furthermore, the composite positive electrode material using the preparation method of the present application also significantly extends the cycle life of the battery.

[0022] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on the positive electrode collector, and the positive electrode film layer includes the composite positive electrode material of the first aspect of the present application, or the composite positive electrode material obtained according to the preparation method of the second aspect of the present application.

[0023] Since the positive electrode plate of the present application adopts the composite positive electrode material of the present application, the secondary battery adopting the positive electrode plate can simultaneously have a higher initial charge and discharge capacity, a higher energy density and a longer cycle performance.

[0024] In any embodiment of the present application, the positive electrode film layer further comprises a conductive agent and a binder, wherein, based on the total weight of the positive electrode film layer, the positive electrode film layer comprises 70 wt % to 97 wt % of a composite positive electrode material, 2 wt % to 20 wt % of a conductive agent and 1 wt % to 25 wt % of a binder. By regulating the proportion of the composite positive electrode material in the positive electrode film layer, the energy density and cycle life of the secondary battery can be further improved.

[0025] A fourth aspect of the present application provides a secondary battery, which includes the positive electrode plate of the third aspect of the present application.

[0026] Since the secondary battery of the present application adopts the positive electrode plate of the present application, it can simultaneously take into account a higher initial charge and discharge capacity, a higher energy density and a longer cycle performance.

[0027] A fifth aspect of the present application provides a battery module, which includes the secondary battery of the fourth aspect of the present application.

[0028] A sixth aspect of the present application provides a battery pack, which includes the battery module of the fifth aspect of the present application.

[0029] A seventh aspect of the present application provides a device comprising at least one of the secondary battery of the fourth aspect of the present application, the battery module of the fifth aspect of the present application, or the battery pack of the sixth aspect of the present application.

[0030] The battery module, battery pack and device of the present application include the secondary battery described in the present application, and thus have at least the same or similar technical effects as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope (SEM) image of a composite positive electrode material provided in one embodiment of the present application.

[0032] Figure 2 This is a SEM image of a cross section of a composite positive electrode material provided in one embodiment of the present application.

[0033] Figure 3 It is a schematic diagram of one embodiment of a secondary battery.

[0034] Figure 4 yes Figure 3 Exploded diagram of .

[0035] Figure 5 is a schematic diagram of an embodiment of a battery module.

[0036] Figure 6 is a schematic diagram of one embodiment of a battery pack.

[0037] Figure 7 yes Figure 6 Exploded diagram of .

[0038] Figure 8 It is a schematic diagram of one embodiment of a device in which a secondary battery is used as a power source. DETAILED DESCRIPTION

[0039] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application is described in detail below in conjunction with specific embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.

[0040] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0041] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number, and "several" in "one or several" means two or more.

[0042] In the description herein, unless otherwise specified, the term "or" is inclusive. That is, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] The above invention summary of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each embodiment, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0044] In order to meet the demand for high energy density of secondary batteries, lithium replenishment technology can be used to increase the active lithium ion content and compensate for the loss of active lithium during the first charge and discharge process of the secondary battery. The main and more mature technology is the negative electrode lithium replenishment process, such as covering the negative electrode surface with a layer of lithium metal by lithium powder or lithium foil. However, the chemical properties of metallic lithium are very active, and the requirements for the environment and equipment are high. There are also high safety risks in the lithium replenishment process. Compared with negative electrode lithium replenishment, the positive electrode lithium replenishment process has higher safety and reduces the requirements for environmental control. The positive electrode lithium replenishment process can be to add lithium-rich transition metal oxides to the positive electrode slurry to prepare a lithium-rich positive electrode. During the battery formation or initial cycle, the lithium-rich material of the positive electrode releases lithium to compensate for the irreversible active lithium loss caused by the formation of SEI film on the negative electrode.

[0045] However, lithium-rich transition metal oxides still have the problem of being highly active and easily reacting with moisture and carbon dioxide in the environment, which reduces the lithium replenishment effect. In addition, impurities introduced by the reaction also reduce the energy density of the battery. The inventors further discovered that the use of carbon materials or metal oxides (such as Al 2 O 3 、TiO 2 、ZrO 2 The surface coating layer is coated with lithium-rich transition metal oxides (such as lithium-rich transition metal oxides) to isolate the external environment and prevent the lithium-rich materials from contacting water and carbon dioxide in the air. However, the preparation process of the surface coating layer is complicated, especially the introduction of non-electrochemically active coating layers also reduces the energy density of the battery. Moreover, the conventional coating layer is not conducive to the release of lithium ions from the internal lithium supplementation material, resulting in limited improvement in the battery cycle life.

[0046] After in-depth research, the inventor provides a composite positive electrode material that uses a coating layer with electrochemical activity to improve the stability of the positive electrode lithium supplement material. Based on this, the composite positive electrode material according to the present application includes a core and a coating layer covering at least a portion of the surface of the core, the core includes the positive electrode lithium supplement material, the positive electrode lithium supplement material includes a lithium-rich metal oxide, and the coating layer includes a positive electrode active material.

[0047] An electrochemically active coating layer means that the coating layer has good ion conductivity, which can provide a good lithium ion deintercalation channel during the battery charging and discharging process. Therefore, during the battery charging process, the coating layer can provide a good lithium ion escape channel for the coated positive electrode lithium replenishment material. Positive electrode active material refers to the material that participates in the embedding and escape of active ions in the positive electrode plate (the electrode plate with higher potential in the battery) during the battery charging and discharging process. The positive electrode lithium replenishment material is usually arranged at the positive electrode and can provide additional active lithium during the first or initial charging of the battery. The positive electrode lithium replenishment material can be used to compensate for the irreversible active lithium loss caused by the formation of SEI film at the negative electrode.

[0048] Positive electrode active materials usually have good stability to moisture and carbon dioxide in the air. In the present application, by coating the surface of the positive electrode lithium replenishing material with the positive electrode active material, it can isolate the external environment, avoid direct contact between the positive electrode lithium replenishing material and moisture and carbon dioxide in the air, reduce surface side reactions, thereby improving the stability of the material, ensuring the purity of the material and the performance of lithium replenishment. At the same time, the positive electrode active material coating layer is a good lithium ion conductor, which is beneficial to the lithium de-lithiation process of the lithium replenishing material and greatly improves the lithium replenishment efficiency. Therefore, the composite positive electrode material of the present application effectively compensates for the active lithium lost during the first charge and discharge process of the battery, improves the first charge and discharge capacity of the battery, and thus enables the battery to obtain a higher energy density. Furthermore, the form of coating the positive electrode lithium replenishing material with the positive electrode active material can avoid the introduction of additional inactive substances, thereby helping the battery to obtain a higher energy density.

[0049] The use of the composite positive electrode material of the present application can also significantly improve the cycle life of the battery. Without being limited by any theory: the composite positive electrode material improves the capacity utilization rate of the positive electrode lithium supplement material, allowing it to release more active lithium. Excess active lithium is embedded in the negative electrode, so that the negative electrode active material is in a certain lithium insertion state, which can alleviate the volume change of the negative electrode active material to a certain extent, thereby reducing the risk of rupture or powder loss of the negative electrode active material, while maintaining good electrolyte wettability and liquid retention rate of the negative electrode electrode sheet. Moreover, this part of active lithium can also be used to make up for the loss of active lithium during the battery cycle in the middle and late stages of the cycle. Therefore, the use of the composite positive electrode material of the present application can have a further extended cycle life.

[0050] In some embodiments, in the composite cathode material, the cathode active material is distributed on the surface of the core in the form of independent particles. The morphology of the composite cathode material can be observed using a scanning electron microscope (eg, SIGMA 300). Figure 1 is a SEM image of a composite cathode material as an example. Figure 2 This is a SEM picture of a cross section of a composite positive electrode material as an example. The cross section of the composite positive electrode material can be obtained using an ion polisher (e.g., an argon ion cross section polisher, such as IB-19500CP). As can be seen from the picture, the composite positive electrode material is a core particle with a large number of positive electrode active material particles coated on the surface.

[0051] In the present application, when the positive electrode lithium replenishing material is distributed on the surface of the positive electrode active material in the form of independent particles, the positive electrode active material on the surface of the composite positive electrode material can form an effective physical barrier to avoid direct contact between the positive electrode lithium replenishing material and the electrolyte, reduce the occurrence of side reactions, and thus further improve the electrochemical stability of the positive electrode lithium replenishing material. At the same time, the positive electrode active material in particle form can also better exert its own high capacity characteristics. Therefore, the battery using the composite positive electrode material can obtain higher energy density and cycle performance.

[0052] Optionally, the core and the coating layer can be bonded by physical bonding (such as intermolecular forces, etc.) or chemical bonding. In some embodiments, in the composite positive electrode material, the bonding of the core and the coating layer is achieved by the intermolecular forces between the positive electrode lithium supplement material particles and the positive electrode active material. In the present application, the positive electrode lithium supplement material and the positive electrode active material are bonded by intermolecular forces, so that the positive electrode active material particles are tightly attached to the surface of the positive electrode lithium supplement material, thereby making the microstructural stability and electrochemical stability of the composite positive electrode material higher. Therefore, the battery using the composite positive electrode material can obtain good long-term cycle performance.

[0053] Optionally, the coverage rate of the positive electrode active material particles on the surface of the positive electrode lithium supplement material is ≥60%. Further optionally, it is ≥70%, ≥80%, ≥90%, ≥95%, or 100%. In the present application, when the coverage rate of the positive electrode active material particles on the surface of the positive electrode lithium supplement material is within the above range, the sensitivity of the composite positive electrode material to the external environment (especially humidity) can be further reduced, the gel problem of the composite positive electrode material in the preparation process of the positive electrode slurry can be effectively improved, and the processability of the composite positive electrode material in the battery application process can be improved.

[0054] In some embodiments, the median particle size D of the positive electrode lithium supplement material is v 50 can be 2 μm to 35 μm. Optionally, D of the positive electrode lithium supplement material v50 is 4 μm to 30 μm, and further optionally is 5 μm to 30 μm, 5 μm to 25 μm, 5 μm to 20 μm, 10 μm to 25 μm, 10 μm to 20 μm, 12 μm to 20 μm, 15 μm to 25 μm, or 15 μm to 20 μm. D of positive electrode lithium supplement material v 50 Within an appropriate range, it can improve the transmission process of lithium ions inside the particles, reduce the ion migration impedance, and at the same time reduce the contact area between the material and the electrolyte, and reduce the side reactions between the electrolyte and the material, thereby improving the utilization rate of the positive electrode lithium supplement material and further improving the energy density and cycle performance of the battery.

[0055] In some embodiments, the median particle size D of the positive electrode active material is v 50 is 0.1 μm to 15 μm. Optionally, D of the positive electrode active material v 50 is 0.2 μm to 10 μm, and further optionally 0.2 μm to 2 μm, 0.2 μm to 5 μm, 0.5 μm to 1.5 μm, 0.8 μm to 1.2 μm, 0.5 μm to 6 μm, 1 μm to 15 μm, 2 μm to 10 μm, 3 μm to 8 μm, 1 μm to 5 μm, or 1 μm to 1.5 μm. D of the positive electrode active material v 50In an appropriate range, the uniformity of the dispersion of the positive electrode active material on the surface of the positive electrode lithium supplement material can be improved, and the agglomeration phenomenon can be reduced. The coating layer formed on the surface of the positive electrode lithium supplement material has a better isolation and protection effect, further improving the material stability, thereby further improving the energy density of the battery. The positive electrode active material is attached to the surface of the positive electrode lithium supplement material, and the positive electrode lithium supplement material can also stabilize the positive electrode active material, greatly alleviating the problem that the positive electrode active material with a smaller particle size is prone to agglomeration during the battery cycle, thereby further improving the battery cycle performance. The positive electrode active material is attached to the surface of the positive electrode lithium supplement material to form larger particles, which can also improve the processing performance of the positive electrode slurry and reduce the physical gel phenomenon, so that a positive electrode sheet with good overall consistency can be prepared to improve the overall performance of the battery. In addition, the appropriate particle size of the positive electrode active material can also improve the transmission performance of active ions in the active material particles, which is conducive to further improving the battery cycle performance.

[0056] In some optional embodiments, the median particle size D of the composite positive electrode material is v 50 is 2 μm to 40 μm, optionally 3 μm to 38 μm, 3 μm to 30 μm, 5 μm to 25 μm, 8 μm to 40 μm, 10 μm to 35 μm, 10 μm to 25 μm, 15 μm to 30 μm, or 10 μm to 20 μm. In the present application, when the median particle size D of the composite positive electrode material is vWhen 50 is within the above range, it is beneficial to improve the compaction density of the positive electrode sheet, thereby improving the energy density of the battery. In addition, the particles in the positive electrode sheet can be in close contact with each other, and a pore structure that is convenient for electrolyte infiltration can be formed, so that the battery can also obtain higher cycle performance.

[0057] In this application, the median particle size (also known as volume average particle size) D of the positive electrode active material, positive electrode lithium supplement material, and composite positive electrode material v 50 is a well-known meaning in the art and can be measured using methods known in the art. For example, it can be measured with a laser particle size analyzer (such as Mastersizer 2000E, Malvern, UK) with reference to GB / T19077-2016 particle size distribution laser diffraction method. v 50 represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%.

[0058] In some embodiments, in the composite positive electrode material, the mass ratio of the positive electrode lithium replenishing material to the positive electrode active material can be 1:2 to 1:35. When the mass ratio of the positive electrode lithium replenishing material to the positive electrode active material is within an appropriate range, a positive electrode active material coating layer of suitable thickness can be formed on the surface of the positive electrode lithium replenishing material, effectively improving the stability of the material, and ensuring that the positive electrode lithium replenishing material in the coating layer can be fully delithiated, ensuring the efficient performance of its lithium replenishing performance. In addition, the composite positive electrode material contains sufficient positive electrode active material, which can enable the positive electrode to have more lithium sites for the reciprocating insertion and extraction of lithium ions, thereby improving the reversible capacity of the battery. Therefore, the battery using the composite positive electrode material can obtain higher energy density and cycle performance.

[0059] Optionally, the mass ratio of the positive electrode lithium supplement material to the positive electrode active material in the composite positive electrode material is 1:5 to 1:30, and further optionally 1:5 to 1:25, 1:10 to 1:20, 1:12 to 1:18, or 1:15 to 1:20. When the mass ratio of the positive electrode lithium supplement material to the positive electrode active material is within the above range, the battery can have a higher energy density and a longer cycle life.

[0060] In the present application, the mass ratio of the positive electrode lithium supplement material to the positive electrode active material in the composite positive electrode material can be tested by a test method known in the art. For example, ICP (inductively coupled plasma) atomic emission spectrometry. The test can be performed in an inductively coupled plasma atomic emission spectrometer (e.g., ICAP7400 from Thermo Fisher Scientific, USA). An exemplary test method is as follows: 2 g of the composite positive electrode material is added to an acid solution (e.g., aqua regia) for digestion, and the digestion can be performed under stirring (e.g., mechanical stirring or microwave stirring, etc.), and the digestion time can be 30 min; the digested solution is added to an ICAP7400 spectrometer to quantitatively analyze the chemical composition elements in the composite positive electrode material. The mass of the compound containing the element is determined by the quantification of each element, and the mass ratio of the positive electrode active material and the positive electrode lithium supplement material is finally calculated.

[0061] It should be noted that the test sample can be directly taken from the composite positive electrode material, or sampled from the positive electrode sheet of the secondary battery for testing. Among them, an exemplary method for obtaining the composite positive electrode material from the secondary battery is as follows:

[0062] (1) Discharge the secondary battery (for safety reasons, the battery is generally fully discharged); disassemble the battery and take out the positive electrode sheet, and soak the positive electrode sheet in dimethyl carbonate (DMC) for a certain period of time (e.g., 2 hours); then take out the positive electrode sheet and dry it at a certain temperature and time (e.g., 80°C, 6 hours), and take out the positive electrode sheet after drying.

[0063] (2) The positive electrode sheet dried in step (1) is baked at a certain temperature and time (e.g., 120° C., 6 h), and a sample of the composite positive electrode material is taken from any area of ​​the baked positive electrode sheet. For example, a blade can be used to scrape the powder for sampling.

[0064] (3) The composite positive electrode material collected in step (2) is sieved (for example, sieved with a 200-mesh sieve) to finally obtain a composite positive electrode material sample that can be used to test the material parameters described in the present application.

[0065] In some embodiments, the lithium-rich metal oxide may be selected from Li 2 M 1 O 2 , Li 2 M 2 O 3 , Li 3 M 3 O 4 , Li 5 M 4 O 4 , Li 6 M 5 O 4The valence state of each metal element except Li in the lithium-rich metal oxide is lower than its own highest oxidation state. 2 M 1 O 2 In, M 1 It may include one or more of Ni, Co, Fe, Mn, Zn, Mg, Ca, and Cu. 1 Including one or more of Ni, Co, Mn, Cu. 1 Including one or more of Ni, Cu, and Mn. As an example, Li 2 M 1 O 2 Can include Li 2 NiO 2 , Li 2 MnO 2 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 , Li 2 Co x2 Mn 1-x2 O 2 Optionally, Li 2 M 1 0 2 Including Li 2 NiO 2 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 Optionally, Li 2 M 1 O 2 Including Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 . Wherein, 0<x1<1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. 0<x2<1. Optionally, 0.1≤x1≤0.9, 0.2≤x1≤0.8, 0.4≤x1≤0.6, or 0.5≤x1≤0.7. Optionally, 0.5≤x2≤0.8.

[0066] In Li 2 M 2 O 3In, M 2 It may include one or more of Mn, Sn, Mo, Ru, and Ir. 2 Including one or more of Mn, Mo, Sn. As an example, Li 2 M 2 O 3 Can include Li 2 MnO 3 , Li 2 MoO 3 One or more of the .

[0067] In Li3M 3 O 4 In, M 3 It may include one or more of V, Nb, Cr, and Mo. Optionally, M 3 It includes one or more of V, Nb, and Mo. As an example, Li 3 M 3 O 4 Can include Li 3 VO 4 , Li 3 NbO 4 , Li 3 MoO 4 Optionally, Li 3 M 3 O 4 Including Li 3 VO 4 , Li 3 NbO 4 One or more of the .

[0068] In Li 5 M 4 O 4 In, M 4 It may include one or more of Fe, Cr, V, and Mo. 4 It includes one or more of Fe, Cr, and V. As an example, Li 5 M 4 O 4 Can include Li 5 FeO 4 , Li 5 CrO 4 , Li 5 VO 4 Optionally, Li 5 M 4 O 4 Including Li 5 FeO 4 .

[0069] In Li 6 M 5 O 4 In, M 5 It may include one or more of Co, V, Cr, and Mo. Optionally, M 5 Including one or more of Co, V, Cr. As an example, Li 6 M 5 O 4 Can include Li 6 CoO 4 , Li 6 VO 4 , Li 6 CrO 4 Optionally, Li 6 M 5 O 4 Including Li 6 CoO 4 .

[0070] In some embodiments, the lithium-rich metal oxide may include Li 2 M 1 O 2 , Li 2 M 2 O 3 , Li 5 M 4 O 4 , Li 6 M 5 O 4 Optionally, the lithium-rich metal oxide may include Li 2 M 1 O 2 , Li 5 M 4 O 4 , Li 6 M 5 O 4 One or more of the following. 1 、M 2 、M 4 、M 5 Respectively as defined herein.

[0071] In some embodiments, the lithium-rich metal oxide may include Li 3 VO 4 , Li 2 MnO 2 , Li 3 NbO 4 , Li 5 FeO 4 , Li 6 CoO4 , Li 2 NiO 2 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 Optionally, the lithium-rich metal oxide includes Li 5 FeO 4 , Li 6 CoO 4 , Li 2 NiO 2 , Li 2 CuO 2 and Li 2 Cu x1 Ni 1-x1-y1 M v1 O 2 Further optionally, the lithium-rich metal oxide includes Li 5 FeO 4 , Li 6 CoO 4 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 One or more of. Wherein, 0<x1<1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.1≤x1≤0.9. Further optionally, 0.2≤x1≤0.8, 0.4≤x1≤0.6, or 0.5≤x1≤0.7.

[0072] In some embodiments, the positive electrode active material may be selected from one or more of layered lithium transition metal oxides, spinel-structured lithium metal oxides, and polyanionic positive electrode materials.

[0073] In some embodiments, the positive electrode active material may include a layered lithium transition metal oxide. Optionally, the layered lithium transition metal oxide is selected from LiCoO 2 、LiNiO 2 、LiMnO 2 、LiNi a Co b Mn c O 2 、LiNi α Co β Al γ O2 , and one or more of their modified materials. Optionally, the layered lithium transition metal oxide includes LiNi a Co b Mn c O 2 、LiNi α Co β Al γ O 2 , and one or more of their modified materials. Wherein, 0<a<1, 0<b<1, 0<c<1, a+b+c=1. Optionally, 0.5≤a≤0.9, or 0.6≤a≤0.85. 0<α<1, 0<β<1, 0<γ<1, α+β+γ=1. Optionally, 0.5≤α≤0.9, or 0.6≤α≤0.85.

[0074] As an example, the layered lithium transition metal oxide may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0 . 2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O 2 One or more of the .

[0075] In the present application, the modification in the modified material may be doping modification or coating modification.

[0076] In some embodiments, the positive electrode active material may include a spinel structured lithium metal oxide, such as lithium manganese oxide, lithium nickel manganese oxide, etc. Specific examples include LiMn 2 O 4 、LiNi 0.5 Mn 1.5 O 4 , and one or more of their modified materials. The modification in the modified material can be doping modification or coating modification.

[0077] In some embodiments, the positive electrode active material may include a polyanionic positive electrode material. The polyanionic positive electrode material is a material comprising lithium, a transition metal and a tetrahedral or octahedral anion structural unit (XO z ) t- wherein X can be selected from P, S, As, Mo, W. For example, X is P. (XO z ) t- It can be (PO 4 ) - The crystal structure of the polyanionic cathode material may be olivine or NASICON. Alternatively, the polyanionic cathode material may include LiFePO 4 (LFP), LiMnPO 4 、LiCoPO 4 、LiNiPO 4 , Li 3 V 2 (PO 4 ) 3 、LiFe y Mn 1-y PO 4 , and one or more of their modified materials, wherein 0<y<1. Optionally, 0.2≤y≤0.8. Further optionally, the positive electrode active material may include LiFePO 4 、LiMnPO 4 , Li 3 V 2 (PO 4 ) 3 , and one or more of their modified materials. As an example, the positive electrode active material includes LiFePO 4 .

[0078] The inventors have found through further research that when the positive electrode active material and the positive electrode lithium supplement material are properly matched, the capacity of the lithium supplement material can be maximized, so that the battery can obtain a higher energy density. Furthermore, the battery can also have better cycle performance.

[0079] In some embodiments, the charge cut-off voltage of the positive electrode active material is 4.2V to 5.2V (vs. Li / Li + ), the lithium-rich metal oxide may be selected from Li 6 CoO 4 , Li 5 FeO 4 , Li 2 NiO 2 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1M y1 O 2 , Li 3 VO 4 , Li 3 NbO 4 Optionally, the lithium-rich metal oxide may be selected from Li 5 FeO 4 , Li 6 CoO 4 , Li 2 NiO 2 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 Further optionally, the lithium-rich metal oxide may be selected from Li 6 CoO 4 , Li 5 FeO 4 , Li 2 NiO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 Further optionally, the lithium-rich metal oxide may be selected from Li 6 CoO 4 , Li 2 NiO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 In some embodiments, the lithium-rich metal oxide includes or is Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 In the formula, 0<x1<1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.1≤x1≤0.9. Further optionally, 0.2≤x1≤0.8, 0.4≤x1≤0.6, or 0.5≤x1≤0.7.

[0080] Alternatively, the positive electrode active material may be selected from LiCoO 2 、LiNiO 2 、LiMnO 2 、LiNi a Co bMn c O 2 、LiNi α Co β Al γ O 2 、LiMn 2 O 4 、LiNi 0.5 Mn 1.5 O 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 And one or more of their modified materials, wherein a, b, c, α, β, γ are as defined herein. Optionally, the positive electrode active material may include LiNi a Co b Mn c O 2 、LiNi α Co β Al γ O 2 , and one or more of their modified materials. Optionally, the positive electrode active material may include LiNi a Co b Mn c O 2 and one or more of its modified materials.

[0081] In these embodiments, optionally, the median particle size D of the positive electrode active material v 50 is 1 μm to 15 μm. Further optionally, D of the positive electrode active material v 50 is 2 μm to 10 μm, 2 μm to 8 μm, 3 μm to 7 μm, 4 μm to 6 μm, 3 μm to 5 μm, or 4 μm to 7 μm. D of the positive electrode active material v 50 Within an appropriate range, it can not only protect the positive electrode lithium supplement material, but also improve the transmission performance of active ions in the particles, while also reducing the side reactions of the electrolyte on the surface of the particles, thereby further improving the capacity and cycle performance of the battery.

[0082] In other embodiments, the charge cut-off voltage of the positive electrode active material is 3.5V to 4.2V (vs. Li / Li + ), the lithium-rich metal oxide is selected from Li 6 CoO 4 , Li 5 FeO 4 , Li 2 NiO 2 , Li 2 CuO 2 , Li2 Cu x1 Ni 1-x1-y1 M y1 O 2 , Li 2 MnO 2 One or more of, wherein 0<x1<1, 0≤y1<0.1, M is selected from one or more of Zn, Sn, Mg, Fe and Mn. Optionally, 0.2≤x1≤0.8; further optionally, 0.5≤x1≤0.8, 0.4≤x1≤0.6, or 0.5≤x1≤0.7. Optionally, the lithium-rich metal oxide is selected from Li 5 FeO 4 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 , Li 2 MnO 2 Further optionally, the lithium-rich metal oxide may be selected from Li 5 FeO 4 , Li 2 CuO 2 , Li 2 Cu x1 Ni 1-x1-y1 M y1 O 2 One or more of the .

[0083] Optionally, the positive electrode active material may be selected from LiFePO 4 , Li 3 V 2 (PO 4 ) 3 and LiFe y Mn 1-y PO 4 One or more of, wherein 0<y<1. Optionally, 0.2≤y≤0.8. Optionally, the positive electrode active material may be selected from LiFePO 4 、LiFe y Mn 1- y PO 4 One or more of the .

[0084] In these embodiments, optionally, the median particle size D of the positive electrode active material v 50 is 0.1 μm to 3.5 μm. Further optionally, D of the positive electrode active material v50 is 0.2 μm to 3 μm, 0.2 μm to 2 μm, 0.5 μm to 1.5 μm, 0.8 μm to 1.2 μm, or 1 μm to 1.5 μm. D of the positive electrode active material v 50 Within an appropriate range, it can not only protect the positive electrode lithium supplement material, but also improve the dispersion performance of the positive electrode active material and the processing performance of the positive electrode slurry, while making the composite active material have good active ion transport performance, thereby further improving the capacity and cycle performance of the battery.

[0085] In the present application, optionally, the inner core lithium-rich metal oxide and the outer layer positive electrode active material have similar charge and discharge voltage ranges, which can ensure that the capacity of the positive electrode active material and the lithium-rich metal oxide of the lithium supplement can be maximized.

[0086] The present application also provides a method for preparing a composite positive electrode material, by which any of the above-mentioned composite positive electrode materials can be obtained.

[0087] The present application provides a method for preparing a composite positive electrode material, comprising the following steps: providing a core, wherein the core comprises a positive electrode lithium replenishing material, wherein the positive electrode lithium replenishing material comprises a lithium-rich metal oxide; providing a coating material, wherein the coating material comprises a positive electrode active material; and coating at least a portion of the surface of the core with the coating material to obtain a composite positive electrode material.

[0088] In the preparation method, the core may be selected from the lithium-rich metal oxides described herein, and the coating material may be selected from the positive electrode active materials described herein.

[0089] In the preparation method, any means that can stably coat the coating material on the core surface can be used. As an example, a mechanical fusion machine can be used for mechanical fusion coating to achieve coating the coating material on the core surface. For example, the core is a positive electrode lithium supplement material, and the coating material is a positive electrode active material. The positive electrode active material and the positive electrode lithium supplement material can form a uniform and firm coating bond through intermolecular forces.

[0090] Optionally, in the mechanical fusion coating process, the high-speed fusion can be carried out at a speed of 200 rpm (revolutions per minute) to 1000 rpm for 1 hour to 10 hours, so that the positive electrode active material is coated on the surface of the positive electrode lithium supplement material to obtain a composite positive electrode material. Optionally, the speed is 300 rpm to 800 rpm. Optionally, the fusion time is 2 hours to 6 hours. The fusion can be carried out at room temperature, for example, 25°C.

[0091] When the positive electrode lithium supplement material or the positive electrode active material also has the D v 50, it can also improve the fusion coating process, reduce the agglomeration of positive electrode active materials, and obtain a uniform and firm coating effect.

[0092] The preparation method of the present application also has the advantages of simple process and easy operation.

[0093] It can be understood that the preferred features and preferred schemes described in the composite positive electrode material of the present application are also applicable to the preparation method of the composite positive electrode material of the present application, and obtain corresponding beneficial effects.

[0094] The present application also provides a secondary battery, which includes a positive electrode plate, wherein the positive electrode plate includes any one or more composite positive electrode materials of the present application. The secondary battery of the present application can simultaneously take into account a higher initial charge and discharge capacity, a higher energy density, and a longer cycle life.

[0095] The secondary battery also includes a negative electrode and an electrolyte. During the charge and discharge process of the secondary battery, active ions are embedded and extracted back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode.

[0096] [Positive electrode]

[0097] The present application provides a positive electrode plate, which includes a positive electrode current collector and a positive electrode film layer arranged on the positive electrode current collector, the positive electrode film layer contains active materials, and the active materials include any one or more composite positive electrode materials of the present application.

[0098] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is laminated on any one or both of the two opposite surfaces of the positive electrode current collector.

[0099] In the positive electrode sheet of the present application, the positive electrode current collector may be made of a material having good electrical conductivity and mechanical strength. As an example, the positive electrode current collector may be made of aluminum foil.

[0100] In the positive electrode sheet of the present application, the positive electrode film layer generally comprises an active material and optionally a binder and optionally a conductive agent, and is generally formed by coating a positive electrode slurry, drying, and cold pressing. The positive electrode slurry is generally formed by dispersing the active material, optionally a conductive agent, and optionally a binder in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP).

[0101] In the positive electrode sheet of the present application, in addition to the composite positive electrode material of the present application, the active material may also include other active materials that can be used for the positive electrode of a secondary battery. Other active materials may include, for example, layered lithium transition metal oxides, olivine-structured lithium-containing phosphates, and one or more of their modified compounds, and for example, include lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium iron vanadium phosphate, and one or more of their modified compounds.

[0102] In some optional embodiments, the positive electrode film layer may contain 70% to 97% by weight of active materials based on the total weight of the positive electrode film layer. Optionally, the weight proportion of active materials in the positive electrode film layer is 85% to 97%, 90% to 97%, or 95% to 97%. By regulating the proportion of active materials in the positive electrode film layer, the energy density and cycle life of the secondary battery can be further improved.

[0103] The binder can stably bind the positive electrode active material and the optional conductive agent to the positive electrode current collector. In some optional embodiments, the positive electrode film layer may contain 1% to 25% by weight of the binder based on the total weight of the positive electrode film layer. Optionally, the weight proportion of the binder in the positive electrode film layer is 1% to 10%, 1% to 5%, or 2% to 5%.

[0104] In some embodiments, the binder of the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and modified polymers thereof.

[0105] The conductive agent can improve the electronic conductivity of the positive electrode film layer. In some optional embodiments, based on the total weight of the positive electrode film layer, the positive electrode film layer may contain 2% to 20% by weight of the conductive agent. Optionally, the weight proportion of the conductive agent in the positive electrode film layer is 2% to 10%, or 2% to 5%.

[0106] In some embodiments, the conductive agent of the positive electrode film layer may include one or more of superconducting carbon, carbon black (such as Super P, acetylene black, Ketjen black), carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0107] It should be noted that the composition or parameters of each positive electrode film layer given in this application refer to the composition or parameter range of the single-sided film layer of the positive electrode current collector. When the positive electrode film layer is arranged on two opposite surfaces of the positive electrode current collector, the composition or parameters of the positive electrode film layer on any one of the surfaces meet the requirements of this application and are considered to fall within the protection scope of this application.

[0108] [Negative electrode]

[0109] The negative electrode plate of the present application includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector.

[0110] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is laminated on any one or both of the two opposite surfaces of the negative electrode current collector.

[0111] The negative electrode current collector may be made of a material with good electrical conductivity and mechanical strength to perform the functions of conducting and collecting current. In some embodiments, the negative electrode current collector may be made of copper foil.

[0112] In the negative electrode sheet of the present application, the negative electrode film layer generally comprises a negative electrode active material and optionally a binder, optionally a conductive agent and other optional additives. It is generally formed by coating a negative electrode slurry on a negative electrode current collector, drying, and cold pressing. The negative electrode slurry coating is generally formed by dispersing the negative electrode active material and optionally a conductive agent, optionally a binder, and optionally a additive in a solvent and stirring evenly. The solvent may be N-methylpyrrolidone (NMP) or deionized water.

[0113] In some embodiments, the negative electrode active material may include one or more of artificial graphite, natural graphite, silicon-based materials, and tin-based materials. Alternatively, the negative electrode active material includes one or more of artificial graphite and natural graphite. Alternatively, the negative electrode active material includes artificial graphite.

[0114] In some embodiments, the conductive agent may include one or more of superconducting carbon, carbon black (eg, Super P, acetylene black, Ketjen black, etc.), carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0115] In some embodiments, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0116] In some embodiments, other optional auxiliary agents include, for example, a thickener (eg, sodium carboxymethyl cellulose CMC-Na), a PTC thermistor material, and the like.

[0117] [Electrolytes]

[0118] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from an electrolyte. The electrolyte includes an electrolyte salt and a solvent.

[0119] In some embodiments, the electrolyte salt may be selected from LiPF 6 (Lithium hexafluorophosphate), LiBF 4 (lithium tetrafluoroborate), LiClO 4 (Lithium Perchlorate), LiAsF 6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl imide), LiTFSI (lithium bis(trifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO 2 F2 One or more of LiFOP (lithium difluorophosphate), LiDFOP (lithium difluorooxalate phosphate) and LiTFOP (lithium tetrafluorooxalate phosphate).

[0120] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0121] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0122] [Isolation film]

[0123] The separator is arranged between the positive electrode and the negative electrode to play a role of isolation. The secondary battery of the present application has no particular restrictions on the type of separator, and any known porous structure separator for secondary batteries can be selected. For example, the separator can be selected from one or more of a glass fiber film, a non-woven film, a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, and a multilayer composite film containing one or more of them.

[0124] The positive electrode sheet, the negative electrode sheet and the isolation film can be made into an electrode assembly through a lamination process or a winding process, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolation role; the electrode assembly is placed in an outer package, injected with electrolyte and sealed to obtain a secondary battery.

[0125] The outer packaging of the secondary battery is used to encapsulate the electrode assembly and the electrolyte. In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0126] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example.

[0127] In some embodiments, reference Figure 4 The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to needs.

[0128] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.

[0129] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0130] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0131] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0132] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0133] The present application also provides a device, which includes at least one of the secondary battery, battery module, or battery pack described in the present application. The secondary battery, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0134] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0135] Figure 8 The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0136] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0137] Example

[0138] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0139] Example 1

[0140] Preparation of lithium-ion secondary batteries:

[0141] Preparation of composite cathode materials

[0142] The positive electrode lithium supplement material is Li 2 Cu 0.6 Ni 0.4 O 2 , median particle size D v 50 is 15μm. The positive electrode active material is LiFePO 4 (lithium iron phosphate, LFP), median particle size D v50 is 1μm. Use mechanical fusion machine for high-speed mechanical fusion coating: the positive electrode lithium supplement material Li 2 Cu 0.6 Ni 0.4 O 2 The positive electrode active material LFP was mixed at a mass ratio of 1:35 and fused at a high speed of 400 rpm for 4 hours to coat the Li 2 Cu 0.6 Ni 0.4 O 2 to obtain a composite positive electrode material.

[0143] Preparation of positive electrode

[0144] The composite positive electrode material, conductive agent carbon black (Super P), and binder PVDF prepared above were dispersed in the solvent NMP at a mass ratio of 97:2:1, and stirred and mixed thoroughly to obtain positive electrode slurry. The positive electrode slurry was coated on the two opposite surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained. Among them, the surface density of the positive electrode film layer was 17.5 mg / cm 2 , compacted density is 2.35g / cm 3 .

[0145] Preparation of negative electrode

[0146] Disperse the negative electrode active material artificial graphite, conductive agent carbon black (Super P), binder styrene butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC-Na) in solvent deionized water at a mass ratio of 96:1.5:1.5:1.0, stir and mix evenly to obtain negative electrode slurry. Coat the negative electrode slurry on the two opposite surfaces of the negative electrode current collector copper foil, dry and cold press to obtain the negative electrode sheet. The surface density of the negative electrode film layer is 8.0 mg / cm 2 , compacted density is 1.65g / cm 3 .

[0147] Preparation of electrolyte

[0148] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed uniformly in a mass ratio of 30:70 to obtain an organic solvent; and lithium salt LiPF 6 Dissolve in the above organic solvent and mix well to obtain an electrolyte solution, wherein LiPF 6 The concentration is 1 mol / L.

[0149] Preparation of secondary batteries

[0150] The positive electrode sheet, the polyethylene (PE) porous isolation film, and the negative electrode sheet are stacked in order, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, injected with electrolyte and packaged to obtain a secondary battery.

[0151] Examples 2 to 30 and Comparative Examples 1 to 6

[0152] The preparation of the secondary battery is similar to that of Example 1, except that the relevant parameters in the preparation of the composite positive electrode material are adjusted, as shown in Table 1; and

[0153] In Examples 26 to 30 and Comparative Examples 4 to 6, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811); the surface density of the positive electrode film is 19.5 mg / cm 2 , compacted density is 3.4g / cm 3 ; The surface density of the negative electrode film is 10.8 mg / cm 2 , compacted density is 1.65g / cm 3 ;

[0154] In Comparative Examples 1 and 4, there is no positive electrode lithium supplementation;

[0155] In Comparative Example 2, the positive electrode lithium supplement material Li 2 Cu 0.6 Ni 0.4 O 2 The positive electrode slurry was prepared by mixing the positive electrode active material LFP at a mass ratio of 1:15, and dispersing the obtained mixed material, the conductive agent SuperP and the binder PVDF in NMP at a mass ratio of 97:2:1;

[0156] In comparative example 3, the positive electrode lithium supplement material Li 2 Cu 0.6 Ni 0.4 O 2 Li obtained by coating with alumina particles 2 Cu 0.6 Ni 0.4 O 2 / Al 2 O 3 (Among which Al 2 O 3 Content 2wt%), the positive electrode lithium supplement material Li 2 Cu 0.6 Ni 0.4 O 2 / Al 2 O 3and the positive electrode active material LFP at a mass ratio of 1:15, and the obtained mixed material, the conductive agent Super P and the binder PVDF at a mass ratio of 97:2:1 are dispersed in NMP to prepare a positive electrode slurry;

[0157] In Comparative Example 5, the positive electrode lithium supplement material Li 2 Cu 0.6 Ni 0.4 O 2 The positive electrode slurry was prepared by mixing the positive electrode active material NCM811 at a mass ratio of 1:20, and dispersing the obtained mixed material, the conductive agent Super P and the binder PVDF in NMP at a mass ratio of 97:2:1;

[0158] In Comparative Example 6, the positive electrode lithium supplement material is Li 2 Cu 0.6 Ni 0.4 O 2 / Al 2 O 3 (Among which Al 2 O 3 Content 2wt%), the positive electrode lithium supplement material Li 2 Cu 0.6 Ni 0.4 O 2 / Al 2 O 3 The positive electrode slurry was prepared by mixing the positive electrode active material NCM811 at a mass ratio of 1:20, and dispersing the obtained mixed material, the conductive agent Super P and the binder PVDF in NMP at a mass ratio of 97:2:1.

[0159] Performance test of secondary batteries:

[0160] At 25°C, charge the secondary battery at a constant current of 1C to the upper cut-off voltage, then charge at a constant voltage to a current of 0.05C, record the charging capacity at this time, which is the first cycle charging capacity; then discharge at a constant current of 1C to the lower cut-off voltage, and then let it stand for 5 minutes. This is a cycle of charging and discharging. Record the discharge capacity at this time, which is the first cycle discharge capacity. Perform the battery charge and discharge test according to the above method, record the discharge capacity of each cycle, until the battery capacity retention rate decays to 80%, and the number of cycles at this time is the cycle life.

[0161] First charge capacity (mAh / g) = first cycle charge capacity / mass of composite positive electrode material contained in the battery

[0162] First discharge capacity (mAh / g) = first cycle discharge capacity / mass of composite positive electrode material contained in the battery

[0163] Capacity retention rate of secondary battery at Nth cycle (%) = Nth cycle discharge capacity / 1st cycle discharge capacity × 100%

[0164] In the test, when the positive electrode active material is LFP, the charge and discharge voltage range of the secondary battery is 2.5V ~ 3.65V; when the positive electrode active material is NCM811, the charge and discharge voltage range of the secondary battery is 2.8V ~ 4.25V.

[0165] Table 1

[0166]

[0167] Note: Unless otherwise specified, the mass ratio in Table 1 is the mass ratio of the positive electrode lithium supplement material to the positive electrode active material.

[0168] It can be seen from the results in Table 1 that the composite positive electrode material of the present application enables the secondary battery to obtain a higher initial charge and discharge capacity, energy density and cycle life by coating the surface of the lithium-rich metal oxide with the positive electrode active material.

[0169] Since Comparative Examples 1 to 6 do not meet the above conditions, the initial charge and discharge capacity, energy density and cycle life of the secondary batteries are all relatively low.

[0170] It can be seen from the results of Examples 1 to 7 that when the ratio of the positive electrode lithium supplement material to the positive electrode active material is within an appropriate range, the energy density and cycle life of the secondary battery can be further improved.

[0171] It can be seen from the results of Examples 5 and 8 to 18 that when the particle size distribution of the positive electrode lithium supplement material or the positive electrode active material is within an appropriate range, the energy density and cycle life of the secondary battery can be further improved.

[0172] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A composite positive electrode material, comprising a core and a coating layer covering at least a portion of the surface of the core, wherein the core comprises a positive electrode lithium supplement material, the positive electrode lithium supplement material comprises a lithium-rich metal oxide, and the coating layer comprises a positive electrode active material, wherein: The positive electrode active material is distributed on the surface of the core in the form of independent particles, and the median particle size D v 50 is 2 μm to 35 μm, and the median particle size Dv50 of the positive electrode active material is 0.1 μm to 15 μm.

2. The composite cathode material according to claim 1, wherein In the composite positive electrode material, the mass ratio of the positive electrode lithium supplement material to the positive electrode active material is 1:2 to 1:

35.

3. The composite cathode material according to claim 2, wherein: The mass ratio of the positive electrode lithium supplement material to the positive electrode active material is 1:5 to 1:

30.

4. The composite cathode material according to claim 3, wherein: The mass ratio of the positive electrode lithium supplement material to the positive electrode active material is 1:10 to 1:

20.

5. The composite cathode material according to claim 1, wherein The median particle size D of the positive electrode lithium supplement material v 50 is 5μm~30μm.

6. The composite cathode material according to claim 5, wherein: The median particle size D of the positive electrode lithium supplement material v 50 is 15μm~25μm.

7. The composite cathode material according to claim 1, wherein The median particle size D of the positive electrode active material v 50 is 0.2μm~10μm.

8. The composite cathode material according to claim 7, wherein The median particle size D of the positive electrode active material v 50 is 0.5μm~6μm.

9. The composite cathode material according to claim 1, wherein The lithium-rich metal oxide is selected from Li2M 1 O2、Li2M 2 O3、Li3M 3 O4、Li5M 4 O4、Li6M 5 One or more of O4, in, M 1 Including one or more of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, M 2 Including one or more of Mn, Sn, Mo, Ru, Ir, M 3 Including one or more of V, Nb, Cr, Mo, M 4 Including one or more of Fe, Cr, V, Mo, M 5 Including one or more of Co, V, Cr, Mo, The valence state of each metal element except Li in the lithium-rich metal oxide is lower than its own highest oxidation valence state.

10. The composite cathode material according to claim 1, wherein The lithium-rich metal oxide is selected from Li3VO4, Li2MnO2, Li3NbO4, Li5FeO4, Li6CoO4, Li2NiO2, Li2CuO2 and Li2Cu x1 Ni 1-x1-y1 M y1 One or more of O2, wherein 0<x1<1, 0≤y1<0.1, and M is selected from one or more of Zn, Sn, Mg, Fe and Mn.

11. The composite cathode material according to claim 10, wherein: 0.2≤x1≤0.8。 12. The composite cathode material according to claim 1, wherein The positive electrode active material is selected from one or more of layered lithium transition metal oxides, spinel-structured lithium metal oxides and polyanion-type positive electrode materials.

13. The composite cathode material according to claim 12, wherein: The layered lithium transition metal oxide is selected from LiCoO2, LiNiO2, LiMnO2, LiNi a Co b Mn c O2、LiNi α Co β Al γ O2 and one or more of their modified materials, wherein 0<a<1, 0<b<1, 0<c<1, a+b+c=1, 0<α<1, 0<β<1, 0<γ<1, α+β+γ=1.

14. The composite cathode material according to claim 12, wherein: The spinel structured lithium metal oxide is selected from LiMn2O4, LiNi 0.5 Mn 1.5 One or more of O4.

15. The composite cathode material according to claim 12, wherein: The polyanion positive electrode material is selected from LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiFe y Mn 1-y One or more of PO4 and their modified materials, wherein 0<y<1.

16. The composite cathode material according to claim 15, wherein: 0.2≤y≤0.8。 17. The composite cathode material according to claim 1, wherein: The positive electrode active material is selected from one or more of LiFePO4, LiMnPO4, Li3V2(PO4)3 and their modified materials.

18. The composite cathode material according to claim 1, wherein: The charging cut-off voltage of the positive electrode active material is 4.2V to 5.2V (vs. Li / Li + ), the lithium-rich metal oxide is selected from Li6CoO4, Li5FeO4, Li2NiO2, Li2Cu x1 Ni 1-x1-y1 M y1 One or more of O2, Li3VO4, Li3NbO4, wherein 0<x1<1, 0≤y1<0.1, and M is selected from one or more of Zn, Sn, Mg, Fe and Mn.

19. The composite cathode material according to claim 18, wherein: 0.1≤x1≤0.9。 20. The composite cathode material according to claim 19, wherein: 0.2≤x1≤0.8。 21. The composite cathode material according to claim 18, wherein The positive electrode active material is selected from LiCoO2, LiNi a Co b Mn c O2、LiNi α Co β Al γ O2, LiMn2O4, LiNi 0.5 Mn 1.5 One or more of O4, LiCoPO4, LiNiPO4 and their modified materials, wherein 0<a<1, 0<b<1, 0<c<1, a+b+c=1, 0<α<1, 0<β<1, 0<γ<1, α+β+γ=1.

22. The composite cathode material according to claim 18, wherein The median particle size D of the positive electrode active material v 50 is 1μm~15μm.

23. The composite cathode material according to claim 22, wherein: The median particle size D of the positive electrode active material v 50 is 2μm~10μm.

24. The composite cathode material according to claim 23, wherein: The median particle size D of the positive electrode active material v 50 is 4μm~6μm.

25. The composite cathode material according to claim 1, wherein: The charging cut-off voltage of the positive electrode active material is 3.5V to 4.2V (vs. Li / Li + ), wherein the lithium-rich metal oxide is selected from Li5FeO4, Li2CuO2, Li2Cu x1 Ni 1-x1-y1 M y1 One or more of O2, Li2MnO2, wherein 0<x1<1, 0≤y1<0.1, and M is selected from one or more of Zn, Sn, Mg, Fe and Mn.

26. The composite cathode material according to claim 25, wherein: 0.1≤x1≤0.9。 27. The composite cathode material according to claim 26, wherein: 0.2≤x1≤0.8。 28. The composite cathode material according to claim 25, wherein The positive electrode active material is selected from LiFePO4, Li3V2(PO4)3 and LiFe y Mn 1-y One or more of PO4, where 0<y<1.

29. The composite cathode material according to claim 28, wherein: 0.2≤y≤0.8。 30. The composite cathode material according to claim 26, wherein The median particle size D of the positive electrode active material v 50 is 0.1μm~3.5μm.

31. The composite positive electrode material according to claim 30, wherein The median particle size D of the positive electrode active material v 50 is 0.2μm~2μm.

32. The composite positive electrode material according to claim 31, wherein The median particle size D of the positive electrode active material v 50 is 0.5μm~1.5μm.

33. The method for preparing a composite positive electrode material according to any one of claims 1 to 32, comprising the following steps: Providing a core, the core comprising a positive electrode lithium supplement material, the positive electrode lithium supplement material comprising a lithium-rich metal oxide; Providing a coating material, wherein the coating material includes a positive electrode active material; The coating material is made to coat at least a portion of the surface of the core to obtain a composite positive electrode material.

34. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer arranged on the positive electrode current collector, wherein the positive electrode film layer comprises the composite positive electrode material according to any one of claims 1 to 32, or the composite positive electrode material obtained according to the preparation method according to claim 33.

35. The positive electrode sheet according to claim 34, wherein: The positive electrode film layer also contains a conductive agent and a binder, wherein, based on the total weight of the positive electrode film layer, the positive electrode film layer contains 70 wt % to 97 wt % of a composite positive electrode material, 2 wt % to 20 wt % of a conductive agent and 1 wt % to 25 wt % of a binder.

36. A secondary battery comprising the positive electrode sheet according to claim 34 or 35.

37. A battery module comprising the secondary battery according to claim 36. 38 . A battery pack comprising the secondary battery according to claim 36 or the battery module according to claim 37 . 39 . An electric device comprising the secondary battery according to claim 36 , the battery module according to claim 37 , or the battery pack according to claim 38 .

Citation Information

Patent Citations

  • Core-shell structure electrochemical active material and preparation method thereof, and battery

    CN112054166A